CEO Compensation in IPOs - Randy Beavers (Cogent Economics & Finance, 2019)
Research Question/Issue: Does inside debt compensation affect previous thought on compensation effects in IPOs? What explains variation in compensation when a company goes public? What is the composition of CEO compensation in an IPO? What types of compensation may be more optimal for or are associated with future financial success for the firm? Research Findings/Insights: Using a sample of 852 IPOs in the United States from 2006 until 2014, we find only one-third of firms have or reported having compensation broken down further into categories of pensions, retirement plans, and deferred compensation. These types of compensation are associated with higher financial success through profitability and asset management. Option compensation remains detrimental to a firm's financial success through lower profitability and worse asset management. Theoretical/Academic Implications: A theoretical compensation model provides and empirically explains 79% of the variation in compensation in IPOs in the first year of the public firm. In addition, this study finds the majority of firms are still inaccurately reporting deferred compensation, at least in the Summary Compensation Table. Future research could look to see why this is the case. Practitioner/Policy Implications: Further investigation and potential litigation by the SEC may be necessary in the future to force firms to place information appropriately in the summary compensation table, especially concerning pension plans, retirement accounts, and other deferred compensation. In addition, individuals on compensation committees may consider giving the CEO more long-term compensation through stock and pensions instead of options.
Keywords: 330; corporate governance; executive compensation; initial public offerings